Pelatihan dan Pendampingan Pembuatan Pupuk Organik dari Limbah Enceng Gondok (Eichhornia Crassipes) dan Kotoran Kambing di Desa Centini, Kabupaten Lamongan - Istiqomah, Istiqomah; Eka Kusumawati, Dian; Ardhana Kisno Saputra, Rifky; Sudarsono, Mahfud; Nur Safitri, Fadila (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Organic waste, such as goat manure and water hyacinth, is abundant and poses environmental challenges if not properly managed. These materials hold potential as raw ingredients for producing organic fertilizer, which can contribute to local economic development. This community service program aims to enhance farmers' skills in converting organic waste into soil-enriching organic fertilizer. The program targeted farmer groups in Centini Village, Laren District, Lamongan Regency. The program's effectiveness was rated high, achieving success in key indicators, including participant attendance, material comprehension, and skill development in waste management into organic fertilizer. Participants also demonstrated an understanding of how to apply organic fertilizer to rice fields and expressed a willingness to independently produce organic fertilizer.